Effect of competitive eukaryotic microorganisms on anti-adhesive activity of Acinetobacter calcoaceticus IMV B-7241 surfactants - Pirog, Tatiana; Ivanov, Mykyta (My University, 2025)
The aim of the study was to investigate the effect of eukaryotic inductors on the antiadhesive activity and biofilm destruction ability of the microbial surfactants synthesized by Acinetobacter calcoaceticus IMV B-7241.Materials and methods. Cultivation of A. calcoaceticus IMV B-7241 was carried out in liquid mineral media containing purified glycerol or waste of biodiesel production (crude glycerol) as substrates. The biological inductors were live and inactivated cells of the yeast Saccharomyces cerevisiae BTM-1, as well as the supernatant after cultivation of the BTM-1 strain. Microbial surfactants were extracted from the culture supernatant using a modified Folch mixture. The antiadhesive activity and the degree of biofilm destruction were determined by spectrophotometric method. Results and discussion. Surfactants synthesized in the presence of all the studied inducers in a medium with glycerol of different quality were more effective anti-adhesive agents compared to surfactants obtained without an inductor. Thus, the adhesion of Proteus vulgaris PA-12, Bacillus subtilis BT-2 and Candida albicans D-6 on steel, tiles and linoleum treated with surfactant solutions synthesized by introducing into the medium with both substrates of all types of inductors was on average 10-70% lower than under the action of surfactants formed without an inductor. The introduction of live S. cerevisiae BTM-1 cells and the corresponding supernatant into a medium with glycerol of different degrees of purification was accompanied by the formation of surfactants, under the influence of which the destruction of biofilms of bacterial test cultures was on average 5-30% higher compared to the use of surfactants synthesized without an inductor. An increase of 12-35% in the destruction of Candida yeast biofilms was observed only under the action of surfactants synthesized in the presence of an inductor in a medium with waste of biodiesel production. Conclusion. The results demonstrate the potential to regulate the anti-adhesive activity of A. calcoaceticus IMV B-7241 surfactants and their ability to destroy biofilms by adding live or inactivated S. cerevisiae BTM-1 yeast cells and the corresponding supernatant to the producer culture medium.

Метою дослідження було вивчення впливу еукаріотичних індукторів на антиадгезивну активність та здатність руйнувати біоплівку мікробних поверхнево-активних речовин, синтезованих Acinetobacter calcoaceticus IMV B-7241. Матеріали та методи. Культивування A. calcoaceticus IMV B-7241 проводили в рідких мінеральних середовищах, що містили очищений гліцерин або відходи виробництва біодизельного палива (сирий гліцерин) як субстрати. Біологічними індукторами були живі та інактивовані клітини дріжджів Saccharomyces cerevisiae BTM-1, а також супернатант після культивування штаму BTM-1. Мікробні поверхнево-активні речовини екстрагували з культурального супернатанту за допомогою модифікованої суміші Фолча. Антиадгезивну активність та ступінь руйнування біоплівки визначали спектрофотометричним методом. Результати та обговорення. Поверхнево-активні речовини, синтезовані у присутності всіх досліджуваних індукторів у середовищі з гліцерином різної якості, були більш ефективними антиадгезивними агентами порівняно з поверхнево-активними речовинами, отриманими без індуктора. Таким чином, адгезія Proteus vulgaris PA-12, Bacillus subtilis BT-2 та Candida albicans D-6 на сталі, плитці та лінолеумі, оброблених розчинами поверхнево-активних речовин, синтезованими шляхом введення в середовище з обома субстратами всіх типів індукторів, була в середньому на 10-70% нижчою, ніж за дії поверхнево-активних речовин, утворених без індуктора. Введення живих клітин S. cerevisiae BTM-1 та відповідного супернатанту в середовище з гліцерином різного ступеня очищення супроводжувалося утворенням поверхнево-активних речовин, під впливом яких руйнування біоплівок бактеріальних тест-культур було в середньому на 5-30% вищим порівняно з використанням поверхнево-активних речовин, синтезованих без індуктора. Збільшення руйнування біоплівок дріжджів Candida на 12-35% спостерігалося лише за дії поверхнево-активних речовин, синтезованих у присутності індуктора, у середовищі з відходами виробництва біодизеля. Висновки. Результати демонструють потенціал для регулювання антиадгезивної активності поверхнево-активних речовин A. calcoaceticus IMV B-7241 та їхньої здатності руйнувати біоплівки шляхом додавання живих або інактивованих клітин дріжджів S. cerevisiae BTM-1 та відповідного супернатанту до середовища культивування продуцента.
Keywords: кафедра біотехнології і мікробіології; поверхнево-активні речовини; адгезія; біоплівка; Acinetobacter calcoaceticus ІМВ В-7241; іnductor; surfactants; adhesion; biofilms